Etablierte und Außenseiter - Elias, Norbert (Suhrkamp, 1990)
Norbert Elias, John L. Scotson: "Etablierte und Außenseiter". Aus dem Englischen von Michael Schröter. Suhrkamp Verlag, Frankfurt am Main 1990. 314 S., geb., 38,- DM